Ratiometric intracellular pH sensors based on nitrogen-doped graphene oxide quantum dots. Issue 5 (May 2022) - Zhang, Xiang; Gu, Yu; Zhang, Yun; Yu, Guo-Yin; Liao, Zhi-Peng; Wu, Hui-Fang; Shi, Chuan-Guo
Abstract: Intracellular pH (pHi) is very essential for the function of cells and organisms. Thus, it is of great scientific and technical significance to develop nanosensors for probing pHi. In this work, nitrogen-doped graphene oxide quantum dots (N-GOQDs) with fluorescent efficiency of 54% are prepared. The fluorescent spectrum excited at 340 nm contains two remarkable bands at 430 and 520 nm. Interestingly, when pH value increases from 3.6 to 10.5, the blue band at 430 nm slightly changes, while the green band at 520 nm significantly quenches. The change of fluorescent intensities also can be reflected by the variation of fluorescent color. The dual-emissive N-GOQDs are developed as ratiometric fluorescent probes for pHi, which can avoid the influence of several deviations, such as probe concentration, optical path length, and detector efficiency. As a proof of concept, pHi of Hela cells is monitored successfully. This work demonstrates the construction of nano-biosensors based on N-GOQDs with bright fluorescence, high-stability, and good biocompatibility. Abstract : Fluorescence; Graphene quantum dots; Optical sensing.